The Latin fifth declension and the Baltic -ē-stems - Piwowarczyk, Dariusz (Baltistica, 2017)
The purpose of this article is to present the history of the comparison made by scholars between the Latin fifth declension and the Baltic -ē-stems and to decide whether both of those formations could go back to a common Indo-European source. It is claimed that the *-eh1- nominal stems did not exist as such in the proto-language and that both the Baltic -ē-stems and the Latin fifth declension are secondary developments of other Indo-European formations.